Sequentially Bornological Compact Space - Fatma Kamil Al-Basri (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper, we introduce the definitions of sequentially bornological continuous mapping and sequentially bornological compact spaces in bornological vector space. We investigate the properties of  these concepts. Also, we give the relation between sequentially bornological compact spaces  and complete bornological vector spaces.